Identification of novel human USP2 inhibitor and its putative role in treatment of COVID-19 by inhibiting SARS-CoV-2 papain-like (PLpro) protease. (December 2020) - Mirza, Muhammad Usman; Ahmad, Sarfraz; Abdullah, Iskandar; Froeyen, Matheus
Graphical abstract: Highlights: SARS-CoV-2 papain-like protease (PLpro) and human ubiquitin carboxyl-terminal hydrolase 2 (USP2) share strikingly similar structural scaffold and conserved catalytic triad. Inhibition of Jurkat and MOLT-4 cell-growth in low micromolar range (≈10 μM) was achieved by a new human USP2 inhibitor (Z93). This is the first account in the on-going COVID-19 outbreak where we purposed the identification of SARS-CoV-2 PLpro inhibitor with a proof of human USP2 inhibition. Abstract: Human ubiquitin carboxyl-terminal hydrolase-2 (USP2) inhibitors, such as thiopurine analogs, have been reported to inhibit SARS-CoV papain-like proteases (PLpro). The PLpro have significant functional implications in the innate immune response during SARS-CoV-2 infection and considered an important antiviral target. Both proteases share strikingly similar USP fold with right-handed thumb–palm–fingers structural scaffold and conserved catalytic triad Cys-His-Asp/Asn. In this urgency situation of COVID-19 outbreak, there is a lack of in-vitro facilities readily available to test SARS-CoV-2 inhibitors in whole-cell assays. Therefore, we adopted an alternate route to identify potential USP2 inhibitor through integrated in-silico efforts. After an extensive virtual screening protocol, the best compounds were selected and tested. The compound Z93 showed significant IC50 value against Jurkat (9.67 μM) and MOTL-4 cells (11.8 μM). The binding mode of Z93 was extensively analyzed through molecular docking, followed by MD simulations, and molecular interactions were compared with SARS-CoV-2. The relative binding poses of Z93 fitted well in the binding site of both proteases and showed consensus π-π stacking and H-bond interactions with histidine and aspartate/asparagine residues of the catalytic triad. These results led us to speculate that compound Z93 might be the first potential chemical lead against SARS-CoV-2 PLpro, which warrants in-vitro evaluations.